Self-focused or other-focused: The influence of acknowledgment type on subsequent donation desires - Wenting, Feng; Xianyun, Shen; Zuowei, Yin (Frontiers in Psychology, 2022)
This study employs morality preference theory to explore how acknowledgment type (self- vs. other-focused) influences donors' subsequent donation desires. The current research consists of 3 studies. Study 1 finds that an other-focused acknowledgment letter elicits higher subsequent donation desires than a self-focused letter. Study 2 testifies to the mediating role of morality preference between the relationship of acknowledgment type and subsequent donation desires. Study 3 manipulates the moral value on “what is the morally right thing of donation” and developed a new scale to measure morality preference. Study 4 excludes the influence of language structure and tests the main effect in a real donation behavior context.